European Union-Latin America : towards a closer association. (1996)
Sets out the guidelines and medium-term objectives for strengthening bi-regional association for the period 1996-2000. Highlights the strategy of the European Union, its priority issues and conditions for trade. Presents the results of the European Summit in Turin on guidelines for the revision of the Maastricht Treaty.
DC